Latin America and the original meaning of fair trade - Coscione, Marco (2015)
The Fairtrade certified fair trade lives today an important internal crisis: its original principles seem increasingly at risk and mixed, often, with interests of stakeholders that have little to do with the social commitment and struggle of those who preceded them. The very meaning of the words fair trade may be changing due to the entry of large multinational companies whose purpose seems rather a fairwashing issue. However, in this scenario, Latin American small producers are taking a greater role on rewriting, from below and from the South, power relations and rules that dominate the global fair circuits.